KERAGAAN BEBERAPA GENOTIPE CABAI (Capsicum annuumL.) DI LAHAN GAMBUT - Siti Julaiha; Elza Zuhry; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Chilli (Capsicum annuum L.) is the one of vegetable commodities that has high economic value.Low productivity chili in Riau caused by several factors, including soil conditions mostly submarginal land such as peatland. This study aimed to obtain the performance chili hybrids from crosses between wrinkled chili and smooth chili that was grown in the peatland to be recommended as a genotype that has a high yield. This study used a randomized block design (RBD), consisting of 8 treatments (IPB C-111xIPB C5, IPB C-111xIPB C19,IPB C-120xIPB-C5,IPB C-120xIPB C-19,IPB C-159xIPB C-5, IPB C-159xIPB C-19, Tanamo, Biola) and 3 replications. The results of this study showed that 8 chili genotypeshad grown in peatland had different potentials between a genotype with others.All chilies genotype showed nonsignificant weight per plant compare to Tanamo and Biola. Genotype ofIPB C120xIPB C-5 is the highest yieldbecause had bigger stem diameter and highest fruit weigth. Keyword : Chili, Genotypes, Performance, Peatland.